Digital Marketing Strategy: Utilizing Social Media Influencers to Reach Target Consumers - Reski Nofrialdi; M. Ridho Mahaputra (Greenation Computer and Information Review, 2024)
Building connections and communicating have become easier thanks to social networking apps and contemporary technologies. The utilization of influencers is a crucial component that propels the prosperity of digital marketing platforms, particularly on social media. Effective marketing tactics try to stimulate sales by matching the products being marketed with the preferences of the target audience. The purpose of this study is to investigate how digital marketing influences customer behavior through social media influencers. AISAS asserts that all types of influencers—micro, macro, and mega—have the ability to produce compelling content that affects a sizable audience's purchasing decisions. An influencer's post likes and comments can be used to determine how the audience feels about them. Influencers use their own verbal and visual lingo to promote products; they frequently use eye-catching images and text. Netizens have the potential to be consumers since they are more likely to look for, buy (act), and evaluate things. This is especially beneficial for companies who use influencer marketing to market their goods. Instagram is expected to have 1,300 million users by April 2023, making it one of the top 3 social media networks worldwide. With 26.6% of adults over 18 using Instagram in Indonesia, Instagram is a valuable tool for influencer marketing. Influencers successfully mold a brand's image, which is why this kind of marketing is becoming more and more common.